System podatkowy jako instrument wspierający zrównoważony rozwój - Dziemianowicz, Ryta Iwona (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
Balanced development, also including rural areas, means the necessity of skillfully combining the laws of ecology and economics, and thus using a set of proper legal and economic regulations, one of those can be a specially created pro-ecological tax system. Taxes play an important part in shaping the price stimulus for both the producers and consumers, and thus can affect the popularization of more environment-friendly technologies, materials or products. The article is an attempt to assess the effectiveness of using tax tools, including the so-called green taxes, in ecological policy. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 68-74